Properties of vanillin and its effects on colorectal cancer in vitro and in vivo - Ho, Ket Li (2011)
Vanillin is responsible for the flavor and smell of vanilla, a widely used flavoring agent. Previous studies showed that vanillin was a good red blood sickle cell inhibitor, anti-microbial agent and anti-mutagen. However, vanillin must be administered at high concentrations and prevented from being oxidized by the upper gastrointestinal tract to be medically effective. Hence, the objectives of this study were: i. to investigate the cytotoxic properties of vanillin on HT-29 colorectal cancer cell line; ii. to assess the negative effect of vanillin when administered at high concentrations in vivo; iii. to investigate the chemopreventive properties of vanillin on colorectal cancer and iv. to study the effects of vanillin on expression of selected genes in vivo. Methods used to study the cytotoxic effects include cytotoxicity assay, double staining cell morphological analysis, cell cycle analysis, apoptosis test and cell proliferation assay. The negative effect of oral and intra-peritoneal administration of vanillin to Sprague-Dawley rats in unoxidized form at high concentrations (150 mg/kg)and 300 mg/kg) was also investigated. Following the administration, animal behavior was observed and recorded. After 14 weeks of vanillin administration, the effects of vanillin on blood cells, kidney, liver and brain were studied. For the chemopreventive properties of vanillin, rats were injected with azoxymethane (AOM) and subsequently treated with vanillin. Aberrant crypt foci (ACF) counts and multiplicity were recorded. RNA was extracted from colon for DNA repair, apoptosis, cell cycle, antiinflammation, proto-oncogene, colorectal cancer biomarker and tumor suppressor gene expressions study. Findings from the in vitro study showed that vanillin was cytotoxic towards HT-29 and 3T3 cells with the IC50 value of 400 μg/ml and 1000 μg/ml respectively. Vanillin also induced apoptosis and cell cycle arrest. Different concentrations of vanillin showed arrest of cell cycle at different checkpoints. G0/G1 arrest was noted at lower concentration of vanillin (200 μg/ml) while G2/M arrest occurred at higher concentration of vanillin (1000 μg/ml). From the in vivo study, results showed that treatment of 300 mg/kg of vanillin by intra-peritoneal injection caused the rats to be unconscious without exerting any negative effect on blood cells, kidney and liver. Further analysis with GenomeLab GeXP genetic system on brain tissues showed that the expression of most xenobiotic metabolism, cell progression, tumour suppressor, DNA damage and inflammation genes was maintained at normal level. However, the expressions of a few xenobiotic metabolism, cell cycle arrest and apoptosis genes were up-regulated by 5 % ethanol injection. This shows that 5% ethanol could pose negative effects onto the brain cells. Nevertheless, when 5 % ethanol was injected together with vanillin, the expression of genes was comparable to normal level. Hence, it is postulated that vanillin might have neuro-protective property. For the chemopreventive effect, AOM-injected rats treated with vanillin have significantly higher (p<0.05) ACF counts and multiplicity compared to the control group. The colon gene expression analysis showed that vanillin could enhance recombinational repair and mismatch repair, arrest cell at cell cycle checkpoints, increase the expression of tumour suppressor gene, colorectal cancer biomarker and proto-oncogene. However, vanillin did not induce apoptosis and inflammation in ACF-bearing colon. In conclusion, vanillin could induce cytotoxic effects on colorectal cancer cells. It was not showing negative effects when administered at high concentrations through oral and intra-peritoneal injections. However, the ACF count and multiplicity indicate that vanillin was a co-mutagen instead of chemopreventive agent in AOM-injected rats. Nevertheless, it should be noted that only intraperitoneally injected vanillin would become co-mutagen, orally administered vanillin is not a co-mutagen.